Novel additive for sperm cryopreservation media: Holotheria parva coelomic cavity extract protects human spermatozoa against oxidative stress—A pilot study. (23rd April 2020) - Khashavi, Zahra; Homaei, Ahmad; Koohnavard, Fahimeh; Kamrani, Ehsan; Spinaci, Marcella; Luwor, Rodney B.; Archang, Mahsa; Agarwal, Ashok; Henkel, Ralf
Abstract: Cryopreservation is the most effective method for preserving semen for a long period of time. However, during the freeze–thaw process, production of reactive oxygen species (ROS) leads to a steep reduction in sperm fertility indices. In this study, we tested the effects of the extract of the coelomic cavity of five Holotheria parva, a marine organism rich in antioxidants, for its ROS‐scavenging activity and cryoprotective effects on oxidative stress. Using a total of 50 semen samples, our results demonstrated that doses of 250 and 500 µg/ml of H. parva coelomic cavity extract significantly increased sperm vitality as compared to the control ( p  < .05). The addition of 250 µg/ml of the extract exerted a significant positive effect on sperm motility. Moreover, sperm DNA damage and ROS production were significantly reduced at extract concentrations of 250 and 500 µg/ml ( p  < .05). To the best of our knowledge, the results of this study represent the first demonstration of the possibility of improving sperm parameters and reducing ROS production and DNA damage by supplementing sperm freezing media with H. parva coelomic extract. Our results suggested that H. parva coelomic extract could be useful for improving the fertilising ability of frozen‐thawed human semen.